LAPTM5 potentiates airway remodeling by regulating MAPKs-mediated airway smooth muscle cells’ dysfunction - Lijiao Jiang; Yaping Ying; Haihong Jin; Tingmin Zhou (Mammalian Genome, 2026)

Revealing spatiotemporal patterns of metro tidal ridership and their relationships with TOD features: A dual-sequence clustering and explainable machine learning approach - Rui An; Zhaomin Tong; Xiping Yang; Yaping Wang; Ying Jing; Yaolin Liu; Lin Luo; Jiayu Liu (Travel Behaviour and Society, 2026)

Next-generation intelligent prepared aquatic dishes: research progress in digital heat control and quality evaluation empowered by industry 4.0 - Ying Xie; Min Zhang; Qi Yu; Yaping Liu (Food Research International, 2026)

Pore-scale heat transfer analysis in grain piles via X-ray CT and LBM - Xiaoliang Wang; Ying Zhou; Yaping Shi; Yanbo Hui; Ju Gao; Yihui Wang; Fan Yang (Journal of Food Engineering, 2026)

Regulation of pH-responsive behavior in electrospun (copper sodium chlorophyllin-alizarin)/fish skin gelatin nanofiber-based hydrogel membranes and their application in real-time intelligent monitoring of fresh shrimp freshness - Botian Zhu; Junru Wang; Hualin Zhang; Haoyou Jiang; Mengmeng Zhao; Yeheng Cao; Yaping Huang; Xuyang Feng; Shuhao Min; Zheng Liu; Ying Wang (Food Bioscience, 2026)

Elevated oxygen partial pressure reduces population exposure to hypoxia over the Qinghai–Xizang Plateau - Yanqiang Chen; Ying Zhang; Yaping Wang; Qinmei Han; Gangfeng Zhang; Xiaoyue Liu; Peijun Shi; Cunrui Huang (Science Bulletin, 2026)

An Advanced Fluorescent Molecularly Imprinted Sensor Based on Carbon Quantum Dots for Highly Sensitive Detection of 6-Mercaptopurine - Yinuo Liu; Zhengyuan Dai; Ying Wang; Shanshan Fu; Li Li; Yaping Ding (Journal of Fluorescence, 2025)

Corrigendum to “Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption” [Chem. Eng. J. 500 (2024) 156655] - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2025)

From victims to protectors: Microalgae's unexpected capacity for diuron elimination - Zhangzhang Xie; Cuiyun Yang; Ju Zhang; Yaping Zhang; Oumei Wang; Ying Wang; Fanghua Liu (Journal of Hazardous Materials, 2025)

Permeability prediction of bulk wheat for storage based on micro-computed tomography and lattice Boltzmann method - Xiaoliang Wang; Ying Zhou; Yaping Shi; Qiao Wang; Yanbo Hui; Haiyang Ding (Biosystems Engineering, 2025)

Research on the spatial correlation network and its driving factors for synergistic development of pollution reduction, carbon reduction, greening, and growth in China's tourism industry - Ying Li; Shizhuan Hao; Yaping Liu; Beilei Chen; Tongqian Zou (Journal of Environmental Management, 2025)

A dual-functional monomer-based molecularly imprinted fluorescent aptasensor employing near-infrared carbon dots for selective detection of quinine in food - Xuyuan Sun; Hao Liu; Zhengyuan Dai; Ying Wang; Li Li; Yaping Ding (Food Chemistry, 2025)

Polyanionic hydrogel electrolytes applied to interface-stabilized zinc ion hybrid capacitors - Pengyun Xie; Xin Wang; Yaping Jiang; Ying Tang; Kaifa Dong; Hui Peng; Guofu Ma; Ziqiang Lei (Chemical Engineering Journal, 2025)

Efficiently catalytic purification of indoor formaldehyde upon Co-N sites derived from ZIF-67 carbonization - Zhaoying Di; Runduo Zhang; Xiaonan Guo; Hanxiao Shen; Sebastien Royer; Jingbo Jia; Ying Wei; Yaping Li; Lirong Zheng (Fuel, 2025)

How does high hydrostatic pressure treatment improve the esterification of quinoa (Chenopodium quinoa Willd.) starch? - Yaping Yin; Yongliang Zhuang; Liping Sun; Ying Gu; Gaopeng Zhang; Xuejing Fan; Yangyue Ding (Food Chemistry, 2025)

Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2024)

Synthesis of P-Rich Carbon Quantum Dots for Sensitive Fluorescent Detection of 2-Methylimidazole - Zhengyuan Dai; Hao Liu; Xuyuan Sun; Ying Wang; Jie Fan; Li Li; Yaping Ding (Journal of Fluorescence, 2024)

Selenium protects against Pb-induced renal oxidative injury in weaning rats and human renal tubular epithelial cells through activating NRF2 - Chongmei Tian; Yu Qiu; Yaping Zhao; Liping Fu; Daozong Xia; Junjie Ying (Journal of Trace Elements in Medicine and Biology, 2024)

Development of food-grade xylanase encapsulation using electrospray dextran microparticles - Yaping Zhang; Chun Liu; Yingjie Lin; Hong Wu; Ying Lin; Fengguang Zhao; Shuangyan Han (Food Hydrocolloids, 2024)

Efficient biostimulation of microbial dechlorination of polychlorinated biphenyls by acetate and lactate under nitrate reducing conditions: Insights into dechlorination pathways and functional genes - Yan Xu; Ying Wang; An Zheng; Yaping Yuan; Lei Xu; Yanqiang Tang; Qingdong Qin (Journal of Hazardous Materials, 2024)

Effects of transition-metal ions on the reduction of N-nitrosodimethylamine in water by zinc - Ying Han; Xiaoping Zheng; Beibei Jiang; Yuling Tang; Hongyuan Liu; Kemin Zhang; Yaping Guo; Jun Li (Journal of Environmental Chemical Engineering, 2024)

Effect of landfill leachate on arsenic migration and transformation in shallow groundwater systems - Ying Zhao; Xinyi Zhang; Zhiqiang Jian; Yaping Gong; Xiaoguang Meng (Environmental Science and Pollution Research, 2023)

Simple and efficient strategy for α-MnO2/C by in-situ synthesis and its performance for degrading urea process wastewater - Yanli He; Shuguang Shen; Ying Wang; Chenyuan Guo; Yaping Yuan; Yaru Fan; Lili Zhang; Yuyan Song (Journal of Environmental Chemical Engineering, 2023)

Fine lithospheric structure controlling Meso-Cenozoic tectono-magmatism in the South China Block: Inference from a multidisciplinary analysis - Feiyu Zhao; Yanhui Suo; Lijun Liu; Xianzhi Cao; Sanzhong Li; Suhua Jiang; Juzhi Deng; Mengxue Dai; Ying Liu; Yaping Hu; Shuzhong Sheng; Bin Hu (Earth-Science Reviews, 2023)

One‐kilometre monthly air temperature and precipitation product over the Mongolian Plateau for 1950–2020 - Ying Xin; Yaping Yang; Xiaona Chen; Xiafang Yue; Yangxiaoyue Liu; Cong Yin (International Journal of Climatology, 2023)
The fragile ecological environment of the Mongolian Plateau (MP) is sensitive to climate change. It is necessary to fully understand the temperature and precipitation changes on the MP to ensure regional sustainable development. Most existing studies are conducted based on station observations which suffer from sparse distribution and limited spatial representativeness and cannot perfectly represent the climatic conditions of the whole region. By contrast, the long‐term, spatially continuous reanalysis products offer new opportunities for MP climate change research. However, the coarse spatial resolution and large uncertainties of reanalysis data limit their applicability to provide reliable climate information at finer scales. Within the delta downscaling framework, we downscale and correct the state‐of‐the‐art European Centre for Medium‐range Weather Forecasts ReAnalysis 5 land portion (ERA5‐Land) using a high‐resolution WorldClim reference climatology and generate a long‐term (1950–2020) 1‐km monthly air temperature and precipitation downscaled dataset. During the downscaling process, the results obtained by nearest neighbour, bilinear and bicubic interpolation methods are evaluated and compared. Air temperature result of bilinear method and precipitation result of nearest neighbour method, which have the best accuracy, are taken as the final downscaled data. The evaluation shows that the downscaled data has acceptable accuracy (overall MBE = −0.41°C, Corr = 0.997, RMSE = 1.51°C for air temperature, and MBE = 1.58 mm·month −1 , Corr = 0.747, RMSE = 24.24 mm·month −1 for precipitation), and outperforms the original ERA5‐Land and widely used Climatic Research Unit (CRU) data. In addition, the downscaled data can also provide accurate and detailed temperature and precipitation change trends over the MP. With fine spatial resolution, long‐time span and good spatial continuity, the downscaled air temperature and precipitation will be a useful data source to explore climate change over the MP.

Structural annotation, semi-quantification and toxicity prediction of pyrrolizidine alkaloids from functional food: In silico and molecular networking strategy - Yaping Xu; Jie Li; Huajian Mao; Wei You; Jia Chen; Hua Xu; Jianfeng Wu; Ying Gong; Lei Guo; Tao Liu; Wuju Li; Bin Xu; et al. (Food and Chemical Toxicology, 2023)

Research on synthesis and property of nano-textured Sc2O3-MgO efficient antibacterial agents - Ying Wang; Yanjing Liu; Xiyue Li; Yuezhou Liu; Fuming Wang; Yaping Huang; Bing Du; Yongfang Qian; Lihua Lv (JBIC Journal of Biological Inorganic Chemistry, 2023)

Disruption of phosphate metabolism and sterol transport-related genes conferring yeast resistance to vanillin and rapid ethanol production - Fengguang Zhao; Yaping Zhang; Jian Hu; Ce Shi; Xiang Ao; Shengding Wang; Ying Lin; Zhongwei Sun; Shuangyan Han (Bioresource Technology, 2023)

Higher pH is associated with enhanced co‐occurrence network complexity, stability and nutrient cycling functions in the rice rhizosphere microbiome - Yaping Guo; Bin Song; Anqi Li; Qi Wu; Haili Huang; Na Li; Ying Yang; Jonathan Miles Adams; Lin Yang (Environmental Microbiology, 2022)
The rice rhizosphere microbiota is crucial for crop yields and nutrient use efficiency. However, little is known about how co‐occurrence patterns, keystone taxa and functional gene assemblages relate to soil pH in the rice rhizosphere soils. Using shotgun metagenome analysis, the rice rhizosphere microbiome was investigated across 28 rice fields in east‐central China. At higher pH sites, the taxonomic co‐occurrence network of rhizosphere soils was more complex and compact, as defined by higher average degree, graph density and complexity. Network stability was greatest at medium pH (6.5

Correction to: Alpinia officinarum mediated copper oxide nanoparticles: synthesis and its antifungal activity against Colletotrichum gloeosporioides - Chunmei Hu; Wenjia Zhu; Ying Lu; Yanfang Ren; Jinyu Gu; Yaping Song; Junyu He (Environmental Science and Pollution Research, 2022)

Alpinia officinarum mediated copper oxide nanoparticles: synthesis and its antifungal activity against Colletotrichum gloeosporioides - Chunmei Hu; Wenjia Zhu; Ying Lu; Yanfang Ren; Jinyu Gu; Yaping Song; Junyu He (Environmental Science and Pollution Research, 2022)

Metagenomics-based antibiotic resistance genes diversity and prevalence risk revealed by pathogenic bacterial host in Taihu Lake, China - Ying Bai; Xiaohong Ruan; Rongfu Li; Yaping Zhang; Zongzhi Wang (Environmental Geochemistry and Health, 2022)

Lead, zinc tolerance mechanism and phytoremediation potential of Alcea rosea (Linn.) Cavan. and Hydrangea macrophylla (Thunb.) Ser. and ethylenediaminetetraacetic acid effect - Yaping Duan; Ying Zhang; Bing Zhao (Environmental Science and Pollution Research, 2022)

Spatio-temporal analysis of urban air pollutants throughout China during 2014–2019 - Chenkai Zhao; Ying Sun; Yaping Zhong; Senhao Xu; Yue Liang; Shu Liu; Xiaodong He; Jinghai Zhu; Takayuki Shibamoto; Miao He (Air Quality, Atmosphere & Health, 2021)

Transcriptomic analysis reveals somatic embryogenesis-associated signaling pathways and gene expression regulation in maize (Zea mays L.) - Meiqi Ding; Haixiao Dong; Yingjie Xue; Shengzhong Su; Ying Wu; Shipeng Li; Hongkui Liu; He Li; Junyou Han; Xiaohui Shan; Yaping Yuan (Plant Molecular Biology, 2020)

Monoclonal Antibody-Based Treatments for Neuromyelitis Optica Spectrum Disorders: From Bench to Bedside - Wenli Zhu; Yaling Zhang; Zhen Wang; Ying Fu; Yaping Yan (Neuroscience Bulletin, 2020)

Neural Stem Cells Transfected with Leukemia Inhibitory Factor Promote Neuroprotection in a Rat Model of Cerebral Ischemia - Lili Tian; Wenli Zhu; Yuanchu Liu; Ye Gong; Aowei Lv; Zhen Wang; Xiaoli Ding; Shaowu Li; Ying Fu; Yi Lin; Yaping Yan (Neuroscience Bulletin, 2019)

Autoantibody to MOG suggests two distinct clinical subtypes of NMOSD - Yaping Yan; Yujing Li; Ying Fu; Li Yang; Lei Su; Kaibin Shi; Minshu Li; Qiang Liu; Aimee Borazanci; Yaou Liu; Yong He; Jeffrey L. Bennett; et al. (Science China Life Sciences, 2016)

Ginsenoside Rg1 protects human umbilical cord blood-derived stromal cells against tert-Butyl hydroperoxide-induced apoptosis through Akt–FoxO3a–Bim signaling pathway - Ying Liu; Long Yi; Lu Wang; Linbo Chen; Xiongbin Chen; Yaping Wang (Molecular and Cellular Biochemistry, 2016)

Isolation and functional characterization of a cold responsive phosphatidylinositol transfer-associated protein, ZmSEC14p, from maize (Zea may L.) - Xiaoyu Wang; Xiaohui Shan; Chunmei Xue; Ying Wu; Shengzhong Su; Shipeng Li; Hongkui Liu; Yuan Jiang; Yanfei Zhang; Yaping Yuan (Plant Cell Reports, 2016)

Fingolimod alters inflammatory mediators and vascular permeability in intracerebral hemorrhage - Yu-Jing Li; Guo-Qiang Chang; Yuanchu Liu; Ye Gong; Chunsheng Yang; Kristofer Wood; Fu-Dong Shi; Ying Fu; Yaping Yan (Neuroscience Bulletin, 2015)

Comparative proteomic analysis of the H99 inbred maize (Zea mays L.) line in embryogenic and non-embryogenic callus during somatic embryogenesis - Lifang Sun; Ying Wu; Hongda Zou; Shengzhong Su; Shipeng Li; Xiaohui Shan; Jinghui Xi; Yaping Yuan (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Analysis of the DNA methylation of maize (Zea mays L.) in response to cold stress based on methylation-sensitive amplified polymorphisms - Xiaohui Shan; Xiaoyu Wang; Guang Yang; Ying Wu; Shengzhong Su; Shipeng Li; Hongkui Liu; Yaping Yuan (Journal of Plant Biology, 2013)

Differential gene expression during somatic embryogenesis in the maize (Zea mays L.) inbred line H99 - Lifang Sun; Ying Wu; Shengzhong Su; Hongkui Liu; Guang Yang; Shipeng Li; Xiaohui Shan; Yaping Yuan (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Association between polymorphisms in the signal transducer and activator of transcription and dilated cardiomyopathy in the Chinese Han population - Ying Peng; Bin Zhou; Yanyun Wang; Yu Chen; Hui Li; Yaping Song; Lin Zhang; Li Rao (Molecular and Cellular Biochemistry, 2012)

Identification and characterisation of candidate genes involved in chilling responses in maize (Zea mays L.) - Guang Yang; Hongda Zou; Ying Wu; Hongkui Liu; Yaping Yuan (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)